A juvenile case of fatty cirrhosis complicated with postoperative hypothalamic hypopituitarism - ARAI, Takayuki; YUASA, Keiichiro; YAMADA, Shoji; KOBAYASHI, Setsuo; TAKEZAWA, Jiro; NAGAMINE, Takeaki; SEKIGUCHI, Toshikazu (Kanzo, 1992)
A 14-year-old female was admitted in our hospital in January 1989. She was diagnosed as praecox puberty in 14 months old. Then a hamartoma was discovered in hypothalamus by CT scan and was resected partially. Her overgrowth continued further, cyproterone acetate had been administered to her since 8 years old. Since 12 years old, her serum GOT, GPT had been elevated, so she was admitted in our hospital for further examination of liver injury and obesity. Laboratory findings and imaging studies suggested hepatic cirrhosis. Endocrinological examination revealed hypothalamic hypopituitarism and obesity. Histology of the liver was compatible with fatty cirrhosis. It can be suggested that obesity and endocrinological abnormality including of use of an anti-androgen drug may be associated with cause of fatty cirrhosis.